THE HISTORY OF EXISTENCE OF THE EMERALD IN THE GRAND DUCHY OF LITHUANIA: MUSEUM VERSION OF THE SECOND EDITION - ČISTIAKOVA, MARINA (Knygotyra, 2012)
The museum version of the Emerald is known in two manuscripts dating to the mid-16th century: the collection No. 1054 of the State Historical Museum, Moscow, and the A. Uvarov collection No. 252. The museum version represents an intermediate stage of the development of the Emerald between the second and third editions. The museum version consists of 202 numbered and 2 unnumbered chapters, 144 out of them coming from the second edition of the Emerald (chs. 21–161 and 180–183) and 60 chapters borrowed from other additional sources (chs. 1–20, 161–179, and 184–202). In the museum version of the second edition of the Emerald, some chapters are missing (chs. 2, 3, 5, 80, 81, 84, 105, 112, 118, 124, 126, 127, 131, 144–147, 151, 161, and 164), although the sequence of the chapters mainly corresponds to that of the second edition (see Appendix). A study of the sources of the additional chapters revealed that five chapters in the museum version had been borrowed from the Serbian Nomocanon edition (chs. 1, 2, 3, 4, and 167), nine chapters came from the Izbornik (Florilegium) of Symeon–Svyatoslav (chs. 186, 187, 189, unnumbered chapter between 189 and 190, as well as chs. 190, 191, 192, and 193), 12 chapters were taken from the Explanatory Palaea (chs. 168–179, The Testaments of The Twelve Patriarchs), 14 chapters belong to the Panegyrikon (chs. 5, 6, 7, 8, 9, 10, 11, 13, 12, 15, 17, 18, 130, and 162); the majority of them are from the Triodian Panegyrikon, including a cycle of homilies for the Holy Week and Easter, worth a separate mention (chs. 7–13). Equally, nine texts were found to come from the Synaxarion (chs. 16, 164, 196, 197, 198, 200, 201, 202, and the following unnumbered chapter). In the museum version of the Emerald, the majority of the short lives of the saints are mainly borrowed from the Synaxarion. Probably at least two Synaxarion manuscripts were used by the compilers, because chapters 164, 196, 197, 198, 200, 201, 202 and the next unnumbered chapter belong to the expanded edition of the Simple Synaxarion, and the Life of Three Vilnius Martyrs is a typical text of the Kiev edition of the Versed Synaxarion created in the Grand Duchy of Lithuania. The presence of the East Slavic edition of the Life of Three Vilnius Martyrs in the museum version of the Emerald leads to the assumption that the aforementioned text was created in the Metropolis of Kiev, because this version of the Life was widespread in the synaxaria and hagiographical collections of the Grand Duchy of Lithuania.